Characterization and evaluation of stable localized corrosion in a 7075-T6 aluminum alloy FSW joint before and after anodizing treatment. (1st November 2022) - Li, Kai; Yang, Hong; Zou, Mengting; Yang, Bingyuan; Xu, Huibin; Zhao, Huaxia; Yin, Henggang; Ma, Yanlong
Abstract: The microstructure and corrosion processes of a friction stir welded (FSW) 7075-T6 aluminum alloy joint, before and after anodizing surface treatment, have been characterized by advanced techniques, and the feasibility of anodizing treatment as a corrosion mitigation method has been evaluated. The results showed that different zones of the FSW joint had distinctly different microstructure and consequently different corrosion behavior in NaCl solution. Stable localized corrosion occurred in the transitional regions between the thermo-mechanically affected zone (TMAZ) and heat affected zone (HAZ), and was characterized by intergranular corrosion. The intergranular corrosion was ascribed to the galvanic coupling effect between Cu-rich grain boundary precipitates and the precipitates free zones (PFZs). Although anodizing and the subsequent sealing treatments could greatly improve the corrosion resistance of the base metal, the TMAZ/HAZ transition regions still showed much higher corrosion susceptibility than other regions. The high corrosion susceptibility of the FSW joint after anodizing treatment is not ascribed to the difference of the anodic oxide film in the regions, but the heterogeneous microstructure of the alloy beneath the anodic film. The present paper has shown that the stable localized corrosion in the FSW joint is intrinsically stemmed from the welding process itself and traditional mitigation method such as anodizing treatment cannot solve the problem; more effective corrosion mitigation methods are still awaited.